OS4.3 The BReMen trial: Patients with benign meningioma - is rehabilitation really necessary?. (19th September 2018) - Kessler, A F; Krause, K; Al-Shameri, B; Weiland, J; Linsenmann, T; Ernestus, R; Hagemann, C; Löhr, M; Jentschke, E
Abstract: Background: Despite the good prognosis of benign meningioma, little is known about eventual impairment of patients' psychological quality of life (pQoL), social and neuropsychological functioning after surgery. These patients might even fail to re-integrate into their private and work environment. Participating in a rehabilitation program (rehab) might be of advantage, but the impact is still undetermined. The BReMen trial ( B elastung und Re habilitation bei Men ingeompatienten) aims to approach these topics. Material and Methods: In a prospective 2-year-follow up trial 80 patients with newly diagnosed meningioma WHO°I are planned to be included. Test time points included pre- (T1), post-surgery (T2), 3, 6, 12 and 24 months post-surgery (T3-T6). Patients` characteristics included: age, gender, educational training, localization/size of meningioma, Barthel-, distress- and work-ability-index, time to return to work.Test batteries focused on pQoL and affect: Short Form-36 Health questionnaire (SF-36), EORTC Quality of Life Questionnaire - Score 30, EORTC Quality of Life Questionnaire for brain tumor patients, PHQ-9 depression score, GAD 7 general anxiety score. Cognitive functioning was meassured by Regensburger Wortflüssigkeitstest, Verbaler Lern- und Merkfähigkeitstest (VLMT), Trail Making Test A and B, Farb-Wort-Test, Aufmerksamkeits-Belastungstest (d2-R) and Wechsler-Memory-Scale-Revised. Results: This interim analysis focused on SF-36 scores, PHQ-9 and distress levels, VLMT and d2-R. So far, 50 patients were recruited, 18 patients dropped out, 32 patients reached T5. 16 of them chose to participate in rehab after surgery, 17 patients refused. Both groups presented an increasing memory function till T5 independently of rehab.Patients with a lower pQoL preferred to enter rehab, improving their SF-36 scores afterwards but again declined at T5. Similarly, patients with a higher depression score also favored rehab with a positive long term effect, thereby declining their distress levels. Additionally, patients showed a higher attention at T5 (d2-R) after rehab compared to T1, while patients without rehab declined. Conclusion: The decline of patients' depression levels and improved attention might reflect the benefit of rehab. However, the re-decline of their pQoL following rehab one year after resection could be a hint for an advantage of long-term neuropsychological support in addition to short term rehab. Hopefully, these questions will be answered with the final analysis of this trial.